That's my turf: An experimental analysis of territorial use rights for fisheries in Indonesia - Carlo Gallier; Jörg Langbein; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
We conduct a framed field experiment in Indonesian fishing communities, with an eye towards evaluating the potential of Territorial Use Rights for Fisheries (TURFs) to preserve coral reef fisheries. Conducted in three culturally distinctive sites, the study assembles groups of five fishers who participate in a common-pool resource game. We implement the game with randomly assigned treatments in all sites to explore whether the extraction decision varies according to three recommended non-binding extraction levels originating from (1) a democratic process, (2) a group leader or (3) an external source that recommends a socially optimal extraction level. In one of the sites - that having the highest levels of ethnic and religious diversity - we find that democratic decision-making as well as information originating from outside the community promotes the cooperative behavior that underpins TURFs, a result that is robust to regressions controlling for individual and community attributes.
Keywords: C93; H43; L31; Q32; 330; Framed field experiment; commons dilemmas; coral reefs; self-governance